Anthropomorphic and biomechanical mockup for abdominal aortic aneurysm. (March 2020) - He, Zinan; Mongrain, Rosaire; Lessard, Simon; Chayer, Boris; Cloutier, Guy; Soulez, Gilles
Highlights: A mechanically, anatomically and pathologically realistic hydrogel-based mockup is developed for AAA. Endovascular repair is performed with this anthropomorphic mockup. The role of AAA surrounding tissue in withstanding intraluminal and abdominal pressure is revealed. The biomechanical constrain imposed by the AAA surrounding tissue during endovascular repair is underlined. Abstract: Abdominal aortic aneurysm (AAA) is an asymptomatic condition due to the dilation of abdominal aorta along with progressive wall degeneration, where rupture of AAA is life-threatening. Failures of AAA endovascular repair (EVAR) reflect our inadequate knowledge about the complex interaction between the aortic wall and medical devices. In this regard, we are presenting a hydrogel-based anthropomorphic mockup (AMM) to better understand the biomechanical constraints during EVAR. By adjusting the cryogenic treatments, we tailored the hydrogel to mimic the mechanical behavior of human AAA wall, thrombus and abdominal fat. A specific molding sequence and a pressurizing system were designed to reproduce the geometrical and diseased characteristics of AAA. A mechanically, anatomically and pathologically realistic AMM for AAA was developed for the first time, EVAR experiments were then performed with and without the surrounding fat. Substantial displacements of the aortic centerlines and vessel expansion were observed in the case without surrounding fat, revealing an essential framework created by the surrounding fat to account for the interactions with medical devices. In conclusion, the importance to consider surrounding tissue for the global deformation of AAA during EVAR was highlighted. Furthermore, potential use of this AMM for medical training was also suggested.